Maybe something beautiful - Campoy, F. Isabel; Howell, Theresa, 1974- (Houghton Mifflin Harcourt, 2016)
"Mira lives in a gray and hopeless urban community until a muralist arrives and, along with his paints and brushes, brings color, joy, and togetherness to Mira and her neighbors"--